Analysis of Robusta Coffee Bean Supply Chain Performance Using SCOR and AHP Methods (Case Study : KSU Buah Ketakasi Sidomulyo): Analisis Kinerja Rantai Pasok Biji Kopi Robusta dengan Metode SCOR and AHP (Studi Kasus : KSU Buah Ketakasi Sidomulyo) - Andika Putra; Danu Indra Wardhana; Ara Nugrahayu Nalawati; Zidan Eka Widianto (Universitas Muhammadiyah Sidoarjo, 2026)
Abstract. Jember Regency is one of the regions with promising prospects in the plantation sector, specifically coffee cultivation. Its coffee production is the second largest in East Java after Malang Regency. Sidomulyo Village, Silo District, has been designated as the leading foreign exchange earner in Jember Regency due to its ability to export coffee. This achievement was made possible through collaboration between the Buah Ketakasi Multipurpose Cooperative (KSU) and several large companies. In 2022, the total harvest of the Buah Ketakasi KSU reached 1,560 tons of green beans. With the rapid development of the global market, demand for coffee commodities has also increased significantly. Therefore, it is crucial to make improvements that can enhance the company's quality. The objectives of this study were (1) to analyze the robusta coffee bean supply chain structure at the Buah Ketakasi KSU in Sidomulyo and (2) to analyze the robusta coffee bean supply chain performance at the Buah Ketakasi KSU in Sidomulyo. This research was conducted at the Buah Ketakasi KSU in Sidomulyo Village, Silo District, Jember Regency. The research was conducted from May to July 2024. The SCOR and AHP methods were used. The results showed two streams in the robusta coffee bean supply chain structure: stream 1, starting with farmers, KSU Buah Ketakasi Sidomulyo, and consumers, while stream 2, starting with farmers, collectors, KSU Buah Ketakasi Sidomulyo, and consumers. Based on the calculations, the total supply chain performance score was 80.854, indicating that KSU Buah Ketakasi Sidomulyo's supply chain performance is at the Average level on a scale of 0-100.